Avaliação da eficácia de limpeza de quatro agulhas irrigadoras endodônticas - Loiola, Lívia Etchebehere de [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP]; Morgental, Renata Dornelles [UNESP]; Tanomaru Filho, Mário [UNESP] (My University, 2011)
The irrigation of root canals aims to their cleaning and disinfection, improving endodontic treatment success. OBJECTIVE: To investigate the influence of the diameter and type of irrigation needle and the root canal enlargement on the mechanical efficacy of endodontic irrigation. MATERIAL AND METHODS: Twelve human single-rooted mandibular incisors were used. During some instrumentation stages (enlargement by #20, #30, and #40 K file), root canals were filled with radiographic contrast solution mixed to propyleneglycol and zinc oxide. Needles with different diameters and designs were employed: G1 – 23G and lateral opening; G2 – 22G and apical opening; G3 – 30G and lateral opening; G4 – 30G and apical opening. The needles were inserted up to resistance, with 1 mm step-back to avoid root canal obliteration. The irrigation was performed with 2 mL of distilled water. Before and after irrigation/aspiration, teeth were radiographed at bucco-lingual and mesiodistal direction, using a digital radiographic system. Then, root canal areas, before (filled by contrast solution) and after irrigation (remnant of contrast solution), were submitted to image subtraction with Adobe Photoshop CS4 software. Subsequently, the areas were measured by Image Tool 3.0 software, allowing the obtaining of the cleaning percentage for each modality. Data were analysed by using Anova and Tukey's test. The level of significance was set at P < 0.05. RESULTS: For all root canal enlargements, 30G needles (G3 e G4) presented a better cleaning efficacy. In all groups, higher cleaning efficacy percentage was observed at #30 and #40 K file enlargement. CONCLUSION: Regardless their design, thinner needles were more effective; a better cleaning efficacy occurred in more enlarged root canals.

A irrigação do canal radicular visa à sua limpeza e desinfecção, contribuindo para o sucesso do tratamento endodôntico. OBJETIVO: Avaliar a influência do diâmetro e tipo de agulha irrigadora e da dilatação do canal radicular na eficácia mecânica da irrigação endodôntica. MATERIAL E MÉTODOS: Utilizaram-se 12 incisivos inferiores humanos com canal radicular único. Durante algumas etapas da instrumentação (dilatação com lima K #20, #30 e #40), os canais radiculares foram preenchidos com solução de contraste radiológico espessada com propilenoglicol e óxido de zinco. Empregaram-se agulhas de diferentes diâmetros e designs: G1 – 23G e abertura lateral; G2 – 22G e abertura apical; G3 – 30G e abertura lateral; G4 – 30G e abertura apical. As agulhas foram inseridas até resistência, com recuo de 1 mm para não obliterar a luz do canal radicular. Realizou-se a irrigação com 2 ml de água destilada. Antes da irrigação/aspiração e após, radiografaramse os dentes nos sentidos vestibulolingual e mesiodistal por intermédio de um sistema radiográfico digital. A seguir, as áreas do canal radicular antes (preenchido pelo contraste) e depois da irrigação (remanescente do contraste) foram submetidas ao método de subtração de imagens pelo programa Adobe Photoshop CS4. Posteriormente, mensuraram-se as áreas por meio do programa Image Tool 3.0, o que possibilitou a obtenção do percentual de limpeza para cada modalidade. A fim de analisar os dados obtidos, recorreu-se à Anova e ao teste de Tukey, com nível de significância de 0,05. RESULTADOS: Para todas as dilatações do canal radicular, as agulhas 30G (G3 e G4) proporcionaram melhor limpeza. Quanto aos grupos, observou-se o maior percentual de limpeza após dilatação com lima K #30 e #40. CONCLUSÃO: Agulhas de menor diâmetro mostraram-se mais eficazes, independentemente do seu design. A limpeza foi maior quando o canal radicular apresentou maior dilatação.
Influence of the endodontic irrigation needle and root canal enlargement on endodontic cleaning efficacy
Keywords: Needles; Endodontics; Root canal irrigants; Agulhas; Endodontia; Irrigantes do canal radicular